Cloning and characterization of norbelladine synthase catalyzing the first committed reaction in Amaryllidaceae alkaloid biosynthesis - Aparna Singh; Marie-Ange Massicotte; Ariane Garand; Laurence Tousignant; Vincent Ouellette; Gervais Bérubé; Isabel Desgagné-Penix (BMC Plant Biology, 2018)
Abstract Background Amaryllidaceae alkaloids (AAs) are a large group of plant-specialized metabolites displaying an array of biological and pharmacological properties. Previous investigations on AA biosynthesis have revealed that all AAs share a common precursor, norbelladine, presumably synthesized by an enzyme catalyzing a Mannich reaction involving the condensation of tyramine and 3,4-dihydroxybenzaldehyde. Similar reactions have been reported. Specifically, norcoclaurine synthase (NCS) which catalyzes the condensation of dopamine and 4-hydroxyphenylacetaldehyde as the first step in benzylisoquinoline alkaloid biosynthesis. Results With the availability of wild daffodil (Narcissus pseudonarcissus) database, a transcriptome-mining search was performed for NCS orthologs. A candidate gene sequence was identified and named norbelladine synthase (NBS). NpNBS encodes for a small protein of 19 kDa with an anticipated pI of 5.5. Phylogenetic analysis showed that NpNBS belongs to a unique clade of PR10/Bet v1 proteins and shared 41% amino acid identity to opium poppy NCS1. Expression of NpNBS cDNA in Escherichia coli produced a recombinant enzyme able to condense tyramine and 3,4-DHBA into norbelladine as determined by high-resolution tandem mass spectrometry. Conclusions Here, we describe a novel enzyme catalyzing the first committed step of AA biosynthesis, which will facilitate the establishment of metabolic engineering and synthetic biology platforms for the production of AAs.